Use of image analysis techniques to determine the embryo size of Senna multijuga (Rich.) seeds and its relation to germination and vigor - José Luís de Marchi; Francisco Guilhien Gomes Junior (Journal of Seed Science, 2017)
Abstract: Semi-automatic evaluations of morphological attributes that are associated to seed germination performance such as the embryo size, have been of great interest when considering the study of image analysis techniques. The objective of this research was to evaluate the accuracy of the Tomato Analyzer software to quantify the variations on the embryo development degree of Senna multijuga seeds (Rich.) and its relationship with germination and tetrazolium tests. Seeds from four lots with different ripeness stages were X-rayed, evaluated according to the embryonic area and submitted to germination and tetrazolium tests. Results from the different parameters showed that the Tomato Analyzer(r) software is sensitive to assess the development degree of Senna multijuga seeds, when expressed by Pericarp Area parameter, but only the Area parameter was directly correlated with the physiological potential of the seed lots.